LEAN METHOD IMPLEMENTATION TO REDUCE OVERCROWDING IN THE EMERGENCY DEPARTMENT: A SYSTEMATIC REVIEW - Asti Arieyani; Dumilah Ayuningtyas (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Throughout the world, emergency departments (ED) are characterized by overcrowding and excessive waiting times. Furthermore, the related delays significantly increase patient mortality and make inefficient use of resources to the detriment of the satisfaction of employees and patients. Lean thinking is a philosophy that focuses on eliminating waste or non-value added elements from the processes so that customers are given greater value. Therefore, many Emergency Departments have begun to apply lean as a way to fight against the problems of crowding, delays and medical incidents. Methods: Eligible studies for this systematic review constitute result summarized that lean method implementation was capable of reducing overcrowding in Emergency Departement. The journal employed in this systematic review sourced from ProQuest, Pubmed, and Google Scholar, whereas the analyzed journals were seven journals. Results: From the total of seven journals reviewed, the studies analyzed the result after implementing the lean method in the Emergency Department. In addition, all of the studies were reported successful in implementing lean intervention. Several studies explained that lean method implementation was capable of reducing waiting time, staying length, and the proportion of patients leaving without being seen in the emergency department. One study suggested that reducing radiography transportation time can reduce turnaround time and can help improve the Emergency Department flow. Conclusion: Lean method implementation can contribute to a decrease in waiting time, stay length, and the proportion of patients leaving without being seen. According to the results of the study, the lean implementation identifies that the lean is capable of decreasing waiting times, stay length, and the proportion of patients leaving without being seen. There must be a policy that governs the lean process. Lean can inspired changes to employee roles, staffing and scheduling, communication and coordination, expertise, workspace layout, and problem-solving. Keywords: Lean, hospital, emergency department, crowds